Factors Influenced Family Values, and Children¡¦s Emotional Inteligence (At Some Primary Schools in Kotamadya Bogor) - Veriati Siregar; Ratna Megawangi; Dwi Hastuti (Media Gizi dan Keluarga, 2000)
The general objective of the study is to determine factors that influence family values and emotional intelligence of school aged children. This study was conducted at SDN Polisi I (group I), SDN Gunung Batu I (group II), and SDN Balumbang Jaya I (group III), Kotamadya Bogor for two months, from June to August 1999. The samples were fourth grade children within the age range of 10 - 11 years old. Data consist of primary and secondary data. Primary data include family identity, housing condition, family socio-economic status, family characteristics, family values and children„Ss emotional intelligence (EQ). Secondary data include facilities of the schools. Data were analized descriptively and statistically using Cronbach¡¦s alpha test, Factor Analisys test, anova test, Chi-square test, Kruskal-Wallis test, Spearmans ¡§rank¡¨ correlation test and multiple regression analysis.Result of the study showed that family values differ between groups in terms of affection, communication, respectfulness and commitment. The only factor influence family values was mother personality. Childrens emotional intelligence includes self emotional awareness, self emotional control, emphaty and the art of keeping relationship are not significant between groups. Factors that influence children¡¦s emotional intelligence (EQ) are value of communication and mothers family history.